COMPUTERIZED INVENTORY SYSTEM DESIGN ON THE STATIONERY DEPARTMENT PU PLANNING AND SUPERVISION OF PROJECT ENGINEERING AND SURROUNDING ROADS JAKARTA - Betty Surya Rosalina; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2002)
Department of public works planning and supervision of the project jakarta technique and its surrounding roads, in managing the stationery supply system uses a special section that is part of the household and equipment / IKMN that examine below the head of administrative affairs. Office stationery supply system managed by the household and equipment / IKMN help each unit in the office to meet the needs of office stationery. but the supply of stationery system is experiencing problems in checking the inventory of ATK still using the cards so that stuff takes a long time and a big risk if the card is lost, and deer, as well as in preparing reports. to overcome these problems, you can use the system via FOD, Diagram Context, Diagram Zero, ERD and Normalization. With a computerized inventory system, design of stationery is expected to assist the household and equipment / IKMN in managing inventories of stationery in the office.